Hubungan antara Kualiti Perkhidmatan dan Kepuasan Pengguna terhadap Perkhidmatan Pengangkutan Awam di KLIA2 - Abd Rahman, Umar Dongoran; Yusoff, Mohd Zarir (Research in Management of Technology and Business, 2023)
Transportation is a necessity for humans to move from one destination to another. Towards the era of modernization, transportation plays an important role in economic growth in a country. However, the failure to provide quality services causes users to be less interested and motivated to use public transport. Inefficient management practices also contribute to low levels of user satisfaction. Therefore, this study aims to identify the level of public transport service quality and its relationship with user satisfaction. SERVQUAL model has been used in this study to evaluate the level of public transport service quality based on 5 dimensions: tangible, reliability, empathy, assurance and responsiveness. This study is focused on users who use public transport services at KLIA2, namely taxis, buses, trains and aeroplanes, with a study sample of 357 respondents. Using a quantitative method, online questionnaires were distributed. In addition, the researcher has used social media applications to distribute questionnaires to public transport users. The study's results show that all objectives and hypotheses have been achieved and accepted. There is a significant positive relationship between the dimensions of service quality and overall user satisfaction. A suggestion for improvement for future studies is the scope of the study, which includes a larger population to obtain validity and more descriptive results. To conclude, the important findings in this study can help the country's transportation and service industry to improve and reprogram strategies to increase user satisfaction.